Pelatihan Pembuatan Pupuk Organik Berbahan Kotoran Sapi Bagi Petani di Kecamatan Sambung Makmur Kabupaten Banjar - Riza Adrianoor Saputra; Jumar Jumar; Anis Wahdi; Rabiatul Wahdah; Muhammad Saifuddin Anshary; Norwinda Norwinda; Irvan Indra Resnawan (Lumbung Inovasi: Jurnal Pengabdian kepada Masyarakat, 2023)
Pengabdian kepada Masyarakat (PKM) ini bertujuan untuk meningkatkan pengetahuan serta keterampilan petani di Kecamatan Sambung Makmur Kabupaten Banjar dalam membuat pupuk organik berbahan kotoran sapi. Khalayak sasaran PKM berupa penyuluhan teknik pembuatan pupuk organik berbahan kotoran sapi dalam rangka menambah ilmu pengetahuan dan keterampilan bagi petani di Kecamatan Sambung Makmur Kabupaten Banjar. Kegiatan PKM dilaksanakan pada 14 Juni 2023, bertempat di BPP Sambung Makmur, Kabupaten Banjar dengan jumlah peserta sebanyak 25 orang yang terdiri dari anggota kelompok tani dan karang taruna di wilayah Kecamatan Sambung Makmur Kabupaten Banjar. Hasil PKM menunjukkan peningkatan pengetahuan dan keterampilan petani di Kecamatan Sambung Makmur Kabupaten Banjar mengenai pembuatan pupuk organik berbahan kotoran sapi. Sebanyak 100% peserta mengetahui apa itu pupuk organik, 100% peserta mengetahui jenis-jenis pupuk organik, 100% peserta mengetahui apa itu pupuk organik kotoran sapi, 100% peserta mengetahui manfaat pupuk organik bagi tanah dan tanaman, 96% peserta mengetahui keunggulan pupuk organik dibanding pupuk kimia, 100% peserta mengetahui bahan-bahan yang digunakan dalam pembuatan pupuk organik kotoran sapi, 100% peserta mengetahui kotoran ternak dapat digunakan sebagai bahan baku pembuatan pupuk organik kotoran sapi, 94% peserta mengetahui proses pembuatan pupuk organik kotoran sapi secara baik dan benar, 88% peserta mengetahui ciri-ciri pupuk organik kotoran sapi yang telah selesai di fermentasi, dan 100% peserta mengetahui cara penggunaan pupuk organik kotoran sapi ke tanaman. Training on Making Organic Fertilizer Made from Cow Manure for Farmers in Sambung Makmur District, Banjar Regency This community service aims to increase the knowledge and skills of farmers in Sambung Makmur District, Banjar Regency, in making organic fertilizer from cow manure. Community service's target audience is in the form of providing information on techniques for making organic fertilizer from cow manure in order to increase knowledge and skills for farmers in Sambung Makmur District, Banjar Regency. The community service activity was carried out on June 14, 2023, at the Sambung Makmur Agricultural Extension Center, Banjar Regency, with a total of 25 participants consisting of members of farmer groups and youth organizations in the Sambung Makmur District, Banjar Regency. The community service results show an increase in the knowledge and skills of farmers in Sambung Makmur District, Banjar Regency, regarding making organic fertilizer from cow manure. As many as 100% of participants know what organic fertilizer is; 100% of participants know the types of organic fertilizer; 100% of participants know what organic cow manure fertilizer is; 100% of participants know the benefits of organic fertilizer for soil and plants; 96% of participants know the advantages of organic fertilizer compared to chemical fertilizers; 100% of participants know the ingredients used in making organic cow manure fertilizer; 100% of participants know that livestock manure can be used as raw material for making organic cow manure fertilizer; and 94% of participants know the process of making organic cow manure fertilizer properly. That's right, 88% of participants know the characteristics of organic cow manure fertilizer that has been fermented, and 100% of participants know how to use organic cow manure fertilizer on plants.